2016
DOI: 10.1128/iai.00671-15
|View full text |Cite
|
Sign up to set email alerts
|

The IL17F and IL17RA Genetic Variants Increase Risk of Cerebral Malaria in Two African Populations

Abstract: jCerebral malaria (CM) is a neurological complication of infection with Plasmodium falciparum that is partly caused by cytokine-mediated inflammation. It is not known whether interleukin-17 (IL-17) cytokines, which regulate inflammation, control the development of CM. To evaluate the involvement of IL-17 cytokines in CM, we analyzed 46 common polymorphisms in IL17A, IL17F, and IL17RA (which encodes the common receptor chain of the members of the IL-17 family) in two independent African populations. A case-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Conversely, the IL-23 / IL-17 immune pathway has been implicated in the development of inflammatory reactions in children that develop severe malarial anaemia [ 21 ], in multi-organ dysfunction and acute renal failure in adult P . falciparum cases from India [ 22 ] and with the risk of cerebral malaria in Africa [ 23 ]. IL-23R haplotypes have also been associated with increased susceptibility to severe malarial anaemia in Kenya [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the IL-23 / IL-17 immune pathway has been implicated in the development of inflammatory reactions in children that develop severe malarial anaemia [ 21 ], in multi-organ dysfunction and acute renal failure in adult P . falciparum cases from India [ 22 ] and with the risk of cerebral malaria in Africa [ 23 ]. IL-23R haplotypes have also been associated with increased susceptibility to severe malarial anaemia in Kenya [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have also shown IL-17 relationship with SMA [ 26 , 27 ]. Apart from these studies linking IL-17 with haemoglobin (Hb) loss, other studies have shown IL-17 to be involved in multiple organ dysfunction [ 28 ], and also found to be associated with higher risk in developing cerebral malaria (CM) [ 29 ]. Since previous studies have reported the recovery of a group of semi-immune mice at low parasitaemia [ 23 , 24 ], and also for the fact that IL-17 was implicated in one study [ 24 ], it is hypothesized that IL-17 is involved in the recovery/protection of the semi-immune mice at low Hb levels.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Th17-related genes were considered as excellent candidate genes for infection diseases. 10 The current study investigated the frequency of IL-17A (rs2275913 and rs3819024), IL-17F (rs763780), and IL-23R (rs11209026 and rs1884444) polymorphisms in a Chinese population with susceptibility to syphilis. 10 The current study investigated the frequency of IL-17A (rs2275913 and rs3819024), IL-17F (rs763780), and IL-23R (rs11209026 and rs1884444) polymorphisms in a Chinese population with susceptibility to syphilis.…”
Section: Expression Levels Of Chemokine/ Chemokine Receptor Gene Mrmentioning
confidence: 99%
“…5,6 T-helper type 17 (Th17) cells, a distinct subset of CD4 + T cells, can induce the expression of interleukin (IL)-23R and secrete IL-17 and other cytokines. [10][11][12][13] The vitamin D receptor (VDR) gene encodes a nuclear receptor for the active form of vitamin D, 1,25-dihydroxy vitamin D3 [1,25(OH) 2 D 3 ]. 7 IL-17, a novel family of proinflammatory cytokines comprising six members: IL-17A to 17F is involved in activation of T cells and maturation of macrophages and dendritic cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation